Etika Berinformasi dalam Al-Qur’an: Upaya Membentuk Masyarakat Demokrasi Ideal - Setiawan, Ahmad Bayu (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2022)
The main reason for the failure of the praxis ideal democratic conception is the absence of a critical society and has the ability to control and maintain objectivity, freedom, and openness of information in the mass media. This is in praxis, indeed democracy turns out to run contrary to the concept of ideal democracy with the mastery of the mass media. Thus, there is an assumption that ordinary people are not capable enough to be well informed. From this research based on Islam and the Quran, it reveals that in realizing an ideal democratic society, a good ability to inform is needed. The Quran in some places has hinted at instructions for mankind, especially Moslem, about the value and ethics of information as in Q.S an-Nisa' verse 83 and al-Hujurat verse 6. By exploring the interpretation of both verses, the author discovers some values and ethics that must be considered in information. The application of these values and ethics will then form a society that is critical in information which then has implications for the formation of a healthy mass media and realizing ideal democratic praxis.